Government in France an introduction to the executive power. - Anderson, Malcolm, 1934- (Governments of Western Europe., 1970)
Governments of Western Europe, Government in France: An Introduction to the Executive Power focuses on the affairs of the government of France. The book first offers information on the history of the French government, including the presidency of the Vth republic. The text also expounds on the role and influence of the prime minister in overseeing the affairs of the government. The selection takes a look at the problems associated with the rational division of administrative tasks and duties in the government. The creation of ministries to ensure efficiency in the affairs of the government is.